The Neurological Impact of Leprosy: Manifestations and Treatment Approaches - Andrea Calderone; Maria Catena Aloisi; Carmela Casella; Salvatore Fiannacca; Bruno Cosenza; Angelo Quartarone; Rocco Salvatore Calabrò (Neurology International)
Background and Objectives: Leprosy primarily affects peripheral nerves, leading to significant neurological complications such as polyneuritis, mononeurosis, and autonomic dysfunction, which contribute to severe disabilities and impaired quality of life for patients. This scoping review aims to investigate the neurological manifestations and main treatments of leprosy patients. Materials and Methods: Studies were identified from an online search of PubMed, Web of Science, Cochrane Library, Embase, and Scopus databases. This review has been registered on OSF (n) PQBYH. Results: Neurological complications of leprosy, such as neuropathy and paralysis, necessitate accurate diagnosis and treatment, as immunological reactions can exacerbate nerve damage. Various studies highlight the effectiveness of personalized therapies, such as corticosteroids, multi-drug therapy (MDT), and surgical interventions, in improving symptoms and neurological function in leprosy patients. Conclusions: Managing neurological complications of leprosy necessitates careful diagnosis and treatment, as many patients experience unresolved peripheral neuropathy despite multidrug therapy. Future research should focus on improving diagnostic tools, exploring the link between neuropathic pain and psychological issues, and developing effective vaccines and treatments to enhance patient outcomes.